Infantile presentation of osteoporosis-pseudoglioma syndrome: A Case Report - Qudsiya Ansari; Anisha Jain; Kailas Randad; Vinaya Singh; Akash Sarkate (Medical Laboratory Journal)
Osteoporosis-pseudoglioma syndrome (OPPG) is a rare disorder characterized by severe osteoporosis and vision impairment, due to mutations in the low-density lipoprotein receptor-related protein 5 (LRP5) gene. This autosomal recessive disorder is characterized by fractures, bone fragility, and pseudoglioma with blindness in infancy. Herein, we present a rare case of OPPG syndrome in an infant who, at 80 days of life (DOL), exhibited multiple fractures without any ophthalmic findings at the time of presentation. This is relatively earlier presentation of the symptoms as fractures are more commonly seen after two years of life.